Inter‐subject stability and regional concentration estimates of 3D‐FID‐MRSI in the human brain at 7 T. (11th August 2021) - Hangel, Gilbert; Spurny‐Dworak, Benjamin; Lazen, Philipp; Cadrien, Cornelius; Sharma, Sukrit; Hingerl, Lukas; Hečková, Eva; Strasser, Bernhard; Motyka, Stanislav; Lipka, Alexandra; Gruber, Stephan; Brandner, Christoph; et al.
Abstract : Purpose: Recently, a 3D‐concentric ring trajectory (CRT)‐based free induction decay (FID)‐MRSI sequence was introduced for fast high‐resolution metabolic imaging at 7 T. This technique provides metabolic ratio maps of almost the entire brain within clinically feasible scan times, but its robustness has not yet been thoroughly investigated. Therefore, we have assessed quantitative concentration estimates and their variability in healthy volunteers using this approach. Methods: We acquired whole‐brain 3D‐CRT‐FID‐MRSI at 7 T in 15 min with 3.4 mm nominal isometric resolution in 24 volunteers (12 male, 12 female, mean age 27 ± 6 years). Concentration estimate maps were calculated for 15 metabolites using internal water referencing and evaluated in 55 different regions of interest (ROIs) in the brain. Data quality, mean metabolite concentrations, and their inter‐subject coefficients of variation (CVs) were compared for all ROIs. Results: Of 24 datasets, one was excluded due to motion artifacts. The concentrations of total choline, total creatine, glutamate, myo‐inositol, and N ‐acetylaspartate in 44 regions were estimated within quality thresholds. Inter‐subject CVs (mean over 44 ROIs/minimum/maximum) were 9%/5%/19% for total choline, 10%/6%/20% for total creatine, 11%/7%/24% for glutamate, 10%/6%/19% for myo‐inositol, and 9%/6%/19% for N ‐acetylaspartate. Discussion: We defined the performance of 3D‐CRT‐based FID‐MRSI for metabolite concentration estimate mapping, showing which metabolites could be robustly quantified in which ROIs with which inter‐subject CVs expected. However, the basal brain regions and lesser‐signal metabolites in particular remain as a challenge due susceptibility effects from the proximity to nasal and auditory cavities. Further improvement in quantification and the mitigation of B 0 / B 1 ‐field inhomogeneities will be necessary to achieve reliable whole‐brain coverage. Abstract : We have assessed the typical amplitude and variability of quantitative concentration estimates of 3D‐CRT‐FID‐MRSI at 7 T in healthy volunteers. We successfully estimated, using an internal water reference, metabolite concentrations in 44 brain ROIs that agree with previous literature and determined inter‐subject coefficients of variation. Our results are a step towards future metabolic high‐resolution atlases of the human brain.